A phase I study of muscadine grape skin extract in men with biochemically recurrent prostate cancer: Safety, tolerability, and dose determination. Issue 14 (27th May 2015) - Paller, Channing J.; Rudek, Michelle A.; Zhou, Xian C.; Wagner, William D.; Hudson, Tamaro S.; Anders, Nicole; Hammers, Hans J.; Dowling, Donna; King, Serina; Antonarakis, Emmanuel S.; Drake, Charles G.; Eisenberger, Mario A.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND New therapies are being explored as therapeutic options for men with biochemically recurrent prostate cancer (BRPC) who wish to defer androgen deprivation therapy. MPX is pulverized muscadine grape (Vitis rotundifolia) skin that contains ellagic acid, quercetin, and resveratrol and demonstrates preclinical activity against prostate cancer cells in vitro. METHODS In the phase I portion of this phase I/II study, non‐metastatic BRPC patients were assigned to increasing doses of MPX (Muscadine Naturals. Inc., Clemmons, NC) in cohorts of two patients, with six patients at the highest dose, using a modified continual reassessment method. Initial dose selection was based on preclinical data showing the equivalent of 500 to 4, 000 mg of MPX to be safe in mouse models. The primary endpoint was the recommended phase II dosing regimen. RESULTS The cohort (n = 14, 71% Caucasian, 29% black) had a median follow‐up of 19.2 (6.2–29.7) months, median age of 61 years, and median Gleason score of 7. Four patients had possibly related gastrointestinal symptoms, including grade 1 flatulence, grade 1 soft stools, and grade 1 eructation. No other related adverse events were reported and one patient reported improvement of chronic constipation. Six of 14 patients came off study for disease progression (five metastatic, one rising PSA) after exposure for a median of 15 months. One patient came off for myasthenia gravis that was unrelated to treatment. Seven patients remain on study. The lack of dose‐limiting toxicities led to the selection of 4, 000 mg/d as the highest dose for further study. Median within‐patient PSADT increased by 5.3 months (non‐significant, P = 0.17). No patients experienced a maintained decline in serum PSA from baseline. CONCLUSION These data suggest that 4, 000 mg of MPX is safe, and exploratory review of a lengthening in PSADT of a median of 5.3 months supports further exploration of MPX. Both low‐dose (500 mg) and high‐dose (4, 000 mg) MPX are being further investigated in a randomized, multicenter, placebo‐controlled, dose‐evaluating phase II trial. Prostate 75:1518–1525, 2015. © 2015 Wiley Periodicals, Inc.